The motor abilities of handball players of different biological maturation - Zivkovic, M.; Stojiljkovic, N.; Antic, V.; Pavlovic, L.; Stankovic, N.; Jorgic, B. (Facta Universitatis: Series Physical Education and Sport, 2019)
The aim of this research was to determine the differences between the results from the tests of motor abilities carried out on a selected group of handball players in relation to their biological maturation. A total of 23 handball players, belonging to a selected group, took part in this research. The overall sample of participants was divided into three groups based on their biological maturation. The measurements of motor abilities were carried out using the following tests: explosive power, sprint speed and rapid changes in direction. The statistical analysis included descriptive statistics, a univariate analysis of variance and the Bonferroni PostHoc test in order to determine whether a statistically significant difference could be detected between the groups on the tests of motor abilities. Based on the statistical analysis (ANOVA method), a difference was determined between the peak height velocity (PHV) groups for all the variables. The PostHoc test later determined that there were no differences for any of the variables between the PrePHV and MidPHV groups. Differences in all the variables were determined between the PrePHV and PostPHV groups. Differences between the MidPHV and PostPHV groups were determined for 7 variables, while no statistically significant difference was determined for 3 of the variables (5JT, T-test and the Slalom). The main contribution of this research is that it indicates to coaches the inevitability of being familiar with the biological maturation of their players for optimal selection, for adequate training design, and a decrease in the risk of injury.